Leveraging AI-Driven Marketing For Ethical Branding In MSMES - Efendri Waruwu; Selvi Agustina (Institut Nalanda, 2023)
This research aims to explore the utilization of AI-driven marketing strategies for fostering ethical branding in Micro, Small, and Medium Enterprises (MSMEs). The research model adopts a qualitative approach, employing in-depth interviews with key stakeholders and content analysis of marketing campaigns. A purposive sampling technique is utilized to select participants from diverse MSMEs. Data analysis involves thematic analysis, identifying patterns and themes related to sustainability, AI integration, and ethical branding practices. The study reveals that MSMEs can effectively leverage AI-driven marketing to enhance their ethical branding initiatives, fostering consumer trust and loyalty while contributing to sustainable development goals. This research underscores the importance of ethical branding strategies driven by AI technologies in enhancing the sustainability agenda within MSMEs.